Associations between neighborhood food environments and deficient protein intake among elderly people in a metropolitan suburb: A case study in Kisarazu city, Japan. Issue 6 (18th July 2017) - Hamamatsu, Yuri; Goto, Chiho; Nishitani, Masaru; Shimadate, Riko; Ueno, Junko; Kusakari, Yoko; Umezaki, Masahiro
Abstract: Objectives: Living in a poor food environment and its association with an increased risk of inadequate nutrient intake are increasingly important issues in Japan due to an increase in the elderly population. Methods: The present study examined the relationships between neighborhood food environment and the protein and fat intakes of elderly Japanese individuals ( n  = 181) living in the metropolitan Tokyo suburb of Kisarazu. Results: A logistic regression analysis adjusted for sociodemographic and shopping behavior variables revealed associations between subjectively evaluated poor neighborhood food environment and deficient protein intake. However, there was no significant association between excessive fat intake and neighborhood food environments. Conclusion: The findings demonstrate that living in a poor neighborhood food environment, which is becoming increasingly prevalent in Japan and other developed countries, has the potential to result in malnutrition, or at least in a low‐quality diet, in elderly populations.